Strategic advances in Vat Photopolymerization for 3D printing of calcium phosphate-based bone scaffolds: A review - Roberto Fagotto-Clavijo; Irene Lodoso-Torrecilla; Anna Diez-Escudero; Maria-Pau Ginebra (Bioactive Materials)
3D-printing has emerged as a leading technology for fabricating personalized scaffolds for bone regeneration. Among the 3D-printing technologies, vat photopolymerization (VP) stands out for its high precision and versatility. It enables the creation of complex, patient-specific scaffolds with advanced pore architectures that enhance mechanical stability and promote cell growth, key factors for effective bone regeneration. This review provides an overview of the advances made in vat photopolymerization printing of calcium phosphates, covering both the fabrication of full ceramic bodies and polymer-calcium phosphate composites. The review examines key aspects of the fabrication process, including slurry composition, architectural design, and printing accuracy, highlighting their impact on the mechanical and biological performance of 3D-printed scaffolds. The need to tailor porosity, pore size, and geometric design to achieve both mechanical integrity and biological functionality is emphasized by a review of data published in the recent literature. This review demonstrates that advanced geometries like Triply Periodic Minimal Surfaces and nature-inspired designs, achievable with exceptional precision by this technology, enhance mechanical and osteogenic performance. In summary, VP's versatility, driven by the diversity of material options, consolidation methods, and precision opens new horizons for scaffold-based bone regeneration.